RANCANG BANGUN SISTEM PEMADAM KEBAKARAN DAN NOTIFIKASI OTOMATIS BERBASIS INTERNET OF THINGS (IOT) - Ritonga, Zabal Rahman; Nopriadi, Nopriadi (LPPM Universitas Putera Batam, 2023)
Today's IOT (Internet Of Things) technology is very popular, with interactions between objects and humans can communicate with each other or objects with objects can also communicate with each other, as well as the application to security in anticipating unexpected fires, or monitoring the situation using early detection sensors, so a smoke detection prototype is made using the MQ-2 sensor and milk detection using the DS18B20 sensor. This detection tool uses Arduino Mega, (MQ-2) and DS18B20, then if there is a fire to extinguish using a Selenoid Valve tool used for water dispensing valves, then to neutralize the air using an Exhaust Fan, this Exhaust Fan is also used to neutralize the air in the room even though there is no smoke detected, The point is to maintain the room temperature so that it is not impermeable and hot in the room, then don't forget also for the notification using two SIM800L notification systems for SMS and NODE MCU ESP32, for NODE MCU ESP32 this uses a Wireless Connection, the two notifications work alternately if one of the notification tools does not work. The method used in this research uses the experimental method. This tool is tested and implemented on a square 50 x 50 cm of hardware and provides the expected and appropriate results. The temperature will be detected above 50°C (Celsius).